Discourse analysis a resource book for students - Jones, Rodney H. 1959- (Routledge, 2019)
Routledge English Language Introductions cover core areas of language study and are one-stop resources for students.Assuming no prior knowledge, books in the series offer an accessible overview of the subject, with activities, study questions, sample analyses, commentaries and key readings - all in the same volume. The innovative and flexible 'two dimensional' structure is built around four sections - introduction, development, exploration and extension - which offer self-contained stages for study. Each topic can also be read across these sections, enabling the reader to build gradually on the knowledge gained. Each book in the series has a companion website with extra resources for teachers, lecturers and students. Discourse Analysis:* provides a comprehensive overview of the major approaches to and methodological tools used in discourse analysis;* introduces both traditional perspectives on the analysis of texts and talk as well as more recent approaches that address technologically mediated and multimodal discourse;* incorporates practical examples using real data;* includes articles from key authors in the field, including Jan Blommaert, William Labov, Paul Baker, Penelope Brown and Stephen Levinson; * is supported by a companion website featuring extra activities, additional guidance, useful links and multimedia examples including sound files and YouTube videos.Features of the new edition include: new readings featuring cutting-edge research; updated references; revised and refreshed examples; and a wider range of material from social media that includes Twitter, Instagram and Snapchat. Written by an experienced teacher and author, this accessible textbook is essential reading for all students of English language and linguistics
Keywords: Englisch; Konversationsanalyse; Diskursanalyse; Lehrbuch